Prospective correlation of the radiological, surgical and pathological findings in patients undergoing cytoreductive surgery for colorectal peritoneal metastases: implications for the preoperative estimation of the peritoneal cancer index. (16th October 2020) - Bhatt, A.; Rousset, P.; Benzerdjeb, N.; Kammar, P.; Mehta, S.; Parikh, L.; Goswami, G.; Shaikh, S.; Kepenekian, V.; Passot, G.; Glehen, O.
Abstract: Aim: The peritoneal cancer index (PCI) is one of the strongest prognostic factors in patients undergoing cytoreductive surgery (CRS) for colorectal peritoneal metastases. Using pathological evaluation, however, the disease extent differs in a large proportion of patients. Our aim was to study the correlation between the radiological (rPCI), surgical (sPCI) and pathological (pPCI) PCI in order to determine factors affecting the discordance between these indices and their potential therapeutic implications. Method: From July 2018 to December 2019, 128 patients were included in this study. The radiological, pathological and surgical findings were compared. A protocol for pathological evaluation was followed at all centres. Results: All patients underwent a CT scan and 102 (79.6%) had a peritoneal MRI. The rPCI was the same as the sPCI in 81 (63.2%) patients and the pPCI in 93 (72.6%). Concordance was significantly lower for moderate‐volume (sPCI 13–20) and high‐volume (sPCI > 20) disease than for low‐volume disease (sPCI 0–12) ( P < 0.001 for sPCI; P = 0.001 for pPCI). The accuracy of imaging in predicting presence/absence of disease upon pathological evaluation ranged from 63% to 97% in the different regions of the PCI. The pPCI concurred with the sPCI in 86 (68.8%) patients. Of the nine patients with sPCI > 20, the pPCI was less than 20 in six. Conclusion: The rPCI and sPCI both concurred with pPCI in approximately two thirds of patients. Preoperative evaluation should focus on the range in which the sPCI lies and not its absolute value. Radiological evaluation did not overestimate sPCI in any patient with high/moderate‐volume disease. The benefit of CRS in patients with a high r/sPCI (> 20) who respond to systemic therapies should be prospectively evaluated.